A comparative analysis of South Africa's minerals-energy complex before 2011 and the current pursuit of a renewable just energy transition post-2011 to 2023 - Khumalo, Sbusiso (Graduate School of Development Policy and Practice, 2025)
This research traces South Africa's energy transition. It examines to what extent South Africa is on a just transition trajectory by comparing the minerals-energy complex and the current transition to renewable energy. It conducts this review of just transition through the lens of “equity” and suggests that “just transition” concerns equity or equitable distribution. It examines if South Africa is on a just transition by researching four dimensions of equity. The dimensions include (a) energy security, (b) the inclusivity of job creation, (c) redress for historical injustices experienced by vulnerable communities, and (d) broad-based empowerment initiatives. This is measured and deduced from the empirical review of the extent to which South Africa's energy sector has undergone or is undergoing a just transition. By systematically evaluating these dimensions, the research found that energy security can only be met if fairly distributed to all, avoiding the repetition of the minerals-energy complex structure which was biased against black people. The current renewable energy transition must ensure that the distribution of energy does not prioritise industrial companies but also supplies low-income households with affordable energy. South Africa's energy sector will need to diverge from the minerals-energy complex's narrow or enclave distributional structure. The sector will only be on a just transition if community protection and broad-based initiatives are mandatory targets to be met by private renewable companies (specifically Independent Power Producers). Lastly, stakeholder alignment is important for a successful just transition embedded in energy policies.